2022
DOI: 10.46542/pe.2022.221.629636
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitudes and practices toward human papillomavirus infection among undergraduate pharmacy students in Saudi Arabia

Abstract: Background: Human papillomavirus (HPV) is one of the most widespread viral infections that affect the reproductive tract. The aim of this study is to assess the knowledge, attitude, and practice toward HPV amongst pharmacy students in Saudi Arabia. Methods: A cross-sectional prospective online survey-based study was conducted amongst all second year to final year students enrolled in the pharmacy programme. Results: Female students exhibited better awareness and knowledge (87.2%) compared to male students (12.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…According to a study conducted in Saudi Arabia, pharmacy students have a lower knowledge about the HPV-related risk of cervical cancer compared to physicians and medical students. 39 Meanwhile, this study showed no significant difference in knowledge related to HPV, cervical cancer, and the HPV vaccine between pharmacy students and non-pharmacy students. This suggests that education on HPV and the HPV vaccine has been widely disseminated to students not only in the pharmacy field but also in other disciplines.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…According to a study conducted in Saudi Arabia, pharmacy students have a lower knowledge about the HPV-related risk of cervical cancer compared to physicians and medical students. 39 Meanwhile, this study showed no significant difference in knowledge related to HPV, cervical cancer, and the HPV vaccine between pharmacy students and non-pharmacy students. This suggests that education on HPV and the HPV vaccine has been widely disseminated to students not only in the pharmacy field but also in other disciplines.…”
Section: Discussionmentioning
confidence: 57%
“…This is particularly important for pharmacy students to develop a more positive perception of the significance of HPV vaccination for cervical cancer prevention. According to the study by Ali et al, undergraduate pharmacy training programs at community pharmacies and extracurricular activities can also enhance the communication skills and awareness of future pharmacists in addressing complications and administering HPV vaccinations within the community in a proactive and effective manner 39 …”
Section: Discussionmentioning
confidence: 99%
“…Thus, their qualifications and proximity to patients make pharmacists major players in the promotion of HPV vaccination. However, several studies conducted in North America concluded that pharmacists have an overall positive perception of HPV vaccination but a general lack of knowledge and information about HPV [ 42 , 47 , 48 , 49 ].…”
Section: Introductionmentioning
confidence: 99%